TI_GERICHTE 52.2019.350 vom 9. Juli 2019 , Acquisto di fondi da parte di persone all'estero. Apertura del procedimento - TI Tribunale d'appello (2019)
Acquisto di fondi da parte di persone all'estero. Apertura del procedimento